(untitled) (Global Journal of Management and Business Research, 2012)
It has been observed that employee turnover, especially amongst public sector organizations, is becoming a problem which costs a lot of money, efforts and energy. This problem might be a major obstacle for HR professionals in formulation of their HR policies. This study aims to identify the main turnover factors in some public sector regulatory authorities and to suggest some employee retention strategies within the Pakistani context. Data was collected by a questionnaire distributed amongst 568 employees, developed on the basis of extensive literature review. The importance of having a retention strategy, which is based on a well articulated human resources management system, was stressed.